Environmental factors in seed germination and defense mechanisms to ensure their perpetuation (Research, Society and Development, 2020)
Environmental, biotic and abiotic factors play a fundamental role in the germination phases of seeds, moreover, it is important to know the ideal conditions in which different forest species germinate and settle in nature. Faced with unfavorable conditions, the germination process of the species can be hindered. To ensure the perpetuation of the species, the seeds develop dormancy process, which is a survival strategy in the face of disturbing situations in the environment. Considering that the seeds of forest species native to the Caatinga germinate under different conditions between each species, it is necessary to develop research that identifies the factors that influence this process, as well as the skills and techniques that the seeds use to ensure their continuity in nature. Thus, it is possible to indicate efficient and fast alternatives for germination, in order to use these techniques in seedling production, recovery of degraded areas or commercialization.